2018
DOI: 10.3389/fendo.2018.00370
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights Into the Interaction Between Transcription Factors and Epigenetic Modifications and the Contribution to the Development of Obesity

Abstract: Objective: The development of obesity is inseparable from genetic and epigenetic factors, and transcription factors (TFs) play an essential role in these two mechanisms. This review analyzes the interaction of TFs with epigenetic modifications and the epigenetic mechanisms underlying peroxisome proliferator-activated receptor (PPAR)γ, an important transcription factor, in the development of obesity.Methods: We describe the relationship between TFs and different epigenetic modifications and illustrate the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 172 publications
(182 reference statements)
0
37
0
1
Order By: Relevance
“…This includes changes in the expression of non-coding RNA (Takada, Kouzmenko & Kato, 2009). Studies have shown that epigenetic modification plays an important role in the occurrence and development of obesity (Kasinska, Drzewoski & Sliwinska, 2016; Huang et al, 2018). With the advancement of RNA sequencing technology, more and more non-coding RNAs related to energy metabolism are recognized as involved in obesity and related metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This includes changes in the expression of non-coding RNA (Takada, Kouzmenko & Kato, 2009). Studies have shown that epigenetic modification plays an important role in the occurrence and development of obesity (Kasinska, Drzewoski & Sliwinska, 2016; Huang et al, 2018). With the advancement of RNA sequencing technology, more and more non-coding RNAs related to energy metabolism are recognized as involved in obesity and related metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Pax transactivation domain-interacting protein promotes the trimethylation of histone 3 lysine 4 (H3K4) and the enrichment of H3K4 methyltransferases in the promoter region to activate PPARγ [134]. Acetylation of H3K9 and H3K27 in the promoter region of PPARγ increases during adipogenesis, together with downregulation of deacetylases, which inhibits adipogenesis [135]. Activated PPARγ upregulates the expression of SET domain bifurcated 8-a histone lysine methyl transferase that monomethylates H4K20, which in turn further enhances the expression of PPARγ, as well as its downstream targets in adipogenesis [135].…”
Section: Epigenetic Modifications In Obesity and Effects On Adipose Tmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor-c (PPARc) is a critical transcription factor in regulating adipogenesis in adipose tissues 4 . PPARc plays important roles in the regulation of lipids, and glucose metabolism and insulin sensitivity [5][6][7] , and thus is associated with the control of obesity and related diseases 7 . There are two isoforms of PPARc -PPARc1 and PPARc2.…”
Section: Introductionmentioning
confidence: 99%